Dynamic Analysis of Friction Stir Welding Joints in Dissimilar Material Plate Structure - Siti Norazila, Zahari; M. S. M., Sani; Nurulakmar, Abu Husain; Ishak, M.; Izzuddin, Zaman (Penerbit Universiti Teknologi Malaysia, 2016)
Friction stir welding (FSW) is a welding process that widely used as a solid state joining process for producing welded structure of similar and dissimilar materials such as aluminum alloy, magnesium etc. FSW process has expanded rapidly in industries including aerospace, automotive and maritime due to several advantages compared to other fusion welding. In this paper, experimental modal analysis (EMA) and normal mode finite element analysis (FEA) of the FSW welded joint structure of materials AA6061 and AA7075 will be carried out to identify dynamic properties. Rigid Body Element (RBE2) in MSC NASTRAN/PATRAN is used to model the welds and their compatibility for representing FSW welded structure also being identified. Model updating is performed to minimize the discrepancy between EMA and FEA. Model updating will be acted as an optimization method and is being presented using the structural optimization capability. Finite model updating could be done in individual components and welded structure. RBE2 connecting element can be used to represent friction stir welding with good accuracy.